The economic benefit analysis to the consumer and utility due to PV generation connected to the radial distribution system - Lincy, G; M. Ponnavaikko, Dr; Lenin Anselm W. A., Dr (International Journal of Engineering and Technology, 2018)
During the recent past, the interest towards adoption of Distributed Generation (DG) has increased dramatically among the electric power system utilities. It has been well established that installation of PV Generation at the load points in a distribution system is excellent advantages for both consumers and the utilities. The question arises whether the maximum beneficiary is the Utility or the consumer and who has to bear the cost. This research analyses the economics of the DG with PV Systems, taking a typical 400V distribution system. A detailed procedure adopted for performing the economic analysis is presented in this paper. Benefits considered includes Saving in the energy losses, Energy substitute by the PV system, Capacity release in the Feeders and the Transformer. The PV system is installed at the selected consumer load points, based on the size and location of the loads. Discounted Cash Flow technique is used to assess the economics of the system, by computing the Internal Rate of Return. The paper presents the advantages of using PV Generating systems in the Power Distribution System, quantifying economic benefits both for the Utilities and for the Customers with supporting data.Â Â